Effect of Different Surface Treatments on Surface Roughness and Vickers Micro-Hardness of Feldspathic Porcelain: An In Vitro Study (Mustansiria Dental Journal, 2024)
Background: Several new all-ceramic systems with superior aesthetic qualities such as translucency similar to natural tooth have been developed over the last two decades in response to the demand for metal-free and more natural-looking restorations. To achieve that, all-ceramic restorations, need characterization and glaze.Materials and methods: Twenty-four layered zirconia discs (10 mm in diameter and 2 mm thickness) were designed by a special Sketchup 3d software program and saved as an (STL) file. All specimens were subjected to the polishing by using 600, 800, and 1200 grit of aluminum oxide paper in sequence. The specimens were divided into three groups each with eight samples (n=8) the first group was treated with glaze (G), the second group was polished with polishing kit (PK), and the third group was polished with polishing diamond paste (DPP). After the surface treatments were performed, the surface roughness was measured by using a profilometer and Vickers microhardness (VHN) was measured by using a digital microhardness tester. The surface characteristics changes were examined using a scanning electron microscope (SEM). Data were statistically tested with one-way ANOVA, Post-hoc Tukey’s test, and Least Significant Difference (LSD). Results: Glazing and polishing techniques significantly affected the (Ra) and VHN of feldspathic ceramic. Group G showed significantly the lowest surface roughness (50±0.26) µm in comparison with groups PK (1.00±0.30) µm and DPP (70±0.42) µm. The largest VHN was obtained in a PK group (658.9±66) and the lowest VHN value was shown with the G group (538.4±36), while the VHN of DPP group was (652.8±66).Conclusions: Glazed surface group had the lowest surface roughness and microhardness compared to the polishing kit and polishing paste groups. Therefore, glazing is recommended for finishing feldspathic porcelain, as it is more clinically acceptable, and it causes less wear to the antagonist's teeth.